Pedagogy of violence and resistance of women: The body as disputed territory - Alpízar Guerrero, Mariana (2020)
This article proposes a theoretical and conceptual approach to understanding the mechanisms in which violence works as a pedagogy that not only represses but molds the bodies, teaching them how to be. Also, it systematizes the macro and micropolitical resistances that women have used historically in order to survive and maintain their autonomy. The perspective from which these concepts are analyzed, the historization is made as well as the use of theory on examples of daily life is feminist, and builds up on the idea that when there has been violence, there has always been resistances. The latter is an essential tool that women have used to bespeak their stories of pain, assume their agency and progressively recover their bodies, which had been a disputed historical territory.